Peran Lingkungan Bahasa (Language Environment) dalam Penguasaan Bahasa Arab di Lembaga Pendidikan - Hasan, Hasan (Pelita: Jurnal Studi Islam Mahasiswa UII Dalwa, 2024)
The language environment plays a crucial role in language acquisition, including Arabic, in educational institutions. This research aims to explore how the language environment can influence students' ability to learn Arabic. Using a qualitative approach, the study analyzes data from various educational institutions offering Arabic language programs. The results show that a supportive environment, including the use of Arabic in daily interactions, has a positive impact on students' language proficiency.